2016
DOI: 10.1007/s10147-016-1061-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between UGT1A1*28*28 genotype and lung cancer in the Japanese population

Abstract: This is the first study to demonstrate a significant association between the homozygous UGT1A1*28 genotype and lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This finding corroborates what was observed by Nishikawa et al ( 2016) [53] in their study of 194 patients with lung cancer, who found that the genotype homozygous TA7/7 increases the risk of developing lung cancer by approximately five times. They observed that squamous cell carcinoma was predominant in the lung cancer patients with genotype homozygous TA7/7 and smoking history, similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…This finding corroborates what was observed by Nishikawa et al ( 2016) [53] in their study of 194 patients with lung cancer, who found that the genotype homozygous TA7/7 increases the risk of developing lung cancer by approximately five times. They observed that squamous cell carcinoma was predominant in the lung cancer patients with genotype homozygous TA7/7 and smoking history, similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…The seven TA-repeats allele of UGT1A1*28 polymorphism underlying GS was investigated in relation to cancers of the endometrium [11], ovary [12], lung [13,14], breast [15], and prostate [16]. However, results of these studies were inconclusive, did not specifically investigate bilirubin as a putative cancer risk factor, and had limited sample size (range of number of cases 129 to 310), with the exception of Horsfall et al, where an inverse association was observed between genetically raised bilirubin levels and lung cancer risk among current smokers [14].…”
Section: Introductionmentioning
confidence: 99%
“…MR addresses unmeasured confounding (e.g., by smoking), which is a major limitation of observational studies [17]. The ten cancer types were investigated in large international consortia and selected based on previous evidence (cancers of the lung, ovary, endometrium, breast, and prostate) [11][12][13][14][15][16] or biological plausibility (pancreatic cancer, renal cell cancer, Hodgkin's lymphoma, melanoma, and neuroblastoma).…”
Section: Introductionmentioning
confidence: 99%